Cervical Brachytherapy Exchange: Steps Toward Oncology Capacity Building in Botswana. (13th June 2014) - Bvochara‐Nsingo, Memory; Grover, Surbhi; Gierga, David P.; Makufa, Remigio; Efstathiou, Jason A.; Dixit, Nayha; Clayman, Rebecca H.; Russell, Anthony H.; Lin, Lilie L.; Kasese, Joseph
Abstract : To help share technical knowledge of brachytherapy and the care of patients with cervical cancer in Botswana, a series of visits was organized by two centers in the United States, Massachusetts General Hospital and the University of Pennsylvania. As a result of those visits, necessary future steps were recognized. Such clinical visits are important for facilitating the exchange of knowledge and learning between institutions in developing and developed countries.